Motivasi Petani Dalam Budidaya Lebah Madu (Apis Cerana) Di Desa Buana Sakti Kabupaten Lampung Timur - Hendra Marti Sya'ban; Christine Wulandari; Rudi Hilmanto (Jurnal Sylva Lestari, 2014)
One of the efforts to increase the production of honey bee (Apis cerana) is by giving motivate to farmer and their family, because it can be done by increasing the income can be taken by honey bee cultivation (Apis cerana) in Buana Sakti village. This research was done from January until March 2013 to know at the level of farmers' motivation and also the factors that has correlation and influence with the farmers' motivation in honey bee (Apis cerana) cultivation. Based on the result of some model simulations in test the motivation of the farmers in honey bee (Apis cerana) cultivation in Buana Sakti village has been become high classification with result 18,78, and factors that has influence of motivation to farmers in honey bee Apis cerana cultivation is an easy in honey bee cultivation 90,7%, an easy of market result honey bee cultivation 90%, frequency to follow socialitation 89,9%, farmer's income 85,9%, and a long of honey bee cultivation 78,8%. Keywords: cultivation, honey bee (Apis cerana), motivation, SPSS